Leadership Challenges and Opportunities of English Language Teaching Managers - Pandey, Shiv Ram; Pandey, Suprima (PPSDP International Journal of Education, 2025)
This study explores the leadership challenges and opportunities faced by English Language Teaching (ELT) managers in Nepal. Using a qualitative phenomenological approach, data were collected through semi-structured interviews with 12 participants, including teachers, head teachers, department heads, and resource persons from Kathmandu and Lalitpur districts. Analysis revealed nine core challenges, termed the ‘9Ms’ Management, Motivation, Material, Machine, Method, Medium, Manpower, Money, and Minute. Despite these challenges, leadership opportunities such as professional development, team collaboration, and innovation emerged. Findings offer insights into leadership development for ELT managers in developing contexts and inform strategies for systemic improvement.